2019
DOI: 10.19173/irrodl.v20i4.4113
|View full text |Cite
|
Sign up to set email alerts
|

Maturity Levels of Student Support E- Services Within an Open Distance E-learning University

Abstract: The University of South Africa (UNISA) is one of the distance education universities that is shifting from open distance learning (ODL) to open distance e-learning (ODeL). UNISA started as a correspondence institution in the 1950s and it has since evolved into an ODeL university. The aim of this research was to assess and determine the maturity levels of UNISA lecturers’ and tutors’ explorations of various forms of e-learning technologies to support students in an ODeL environment. Semi-structured interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
2
14
0
1
Order By: Relevance
“…Better quality of e-service can encourage students for learning through an online system. Consistent with the current study Nsamba (2019) elaborated that the e-service quality affects directly to the loyalty of e-learning students. In line with the current study, various prior studies also highlighted that e-service quality has a positive effect on student e-learning (Khodadad Hoseiny et al, 2013;Mart ınez-Arg€ uelles et al, 2009;Zeglat et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Better quality of e-service can encourage students for learning through an online system. Consistent with the current study Nsamba (2019) elaborated that the e-service quality affects directly to the loyalty of e-learning students. In line with the current study, various prior studies also highlighted that e-service quality has a positive effect on student e-learning (Khodadad Hoseiny et al, 2013;Mart ınez-Arg€ uelles et al, 2009;Zeglat et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Another case study, conducted by Zawada (2019:15), notes that Unisa has a complex Quality Assurance (QA) system in place, however, its “effective implementation may not be evenly spread across the institution”. In line with Nsamba’s (2019) and Zawada’s (2019) argument, this paper argues that ODeL and DE institutions can improve the enactment of a high-quality culture of teaching and learning with the student and lecturers at the centre of meaning-making and success. Thus, the focus of this study is to assist students and lecturers via eLearning technologies to reduce TD; which arguably debilitates meaningful learning.…”
Section: Introductionmentioning
confidence: 74%
“…Despite attempts in the literature to understand how meaningful learning occurs between lecturers and students, this action study attempts to use eLearning technologies to support students in their learning and seeks to understand how these technologies can bridge the TD between both stakeholders at the University of South Africa (Unisa). A pertinent study conducted by Nsamba (2019) at Unisa, aimed at assessing the maturity levels of lecturers and tutors’ explorations of different forms of eLearning technologies to support students. The study found that the use of eLearning technologies by lecturers and tutors was measured at level 1 or ‘basic’ on the Maturity Assessment Framework for ODeL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on e-services have looked at various aspects of e-service quality. E-services provided by the university include various electronic services that require no face-to-face or physical interaction between learners and the university, such as electronic registration, electronic payment, electronic seminars or tutorials, and live forums with tutors (Nsamba, 2019). Yoo and Donthu (2001) developed SITEQUAL, a psychometric measure of service quality for online shopping websites.…”
Section: Perceived E-service Qualitymentioning
confidence: 99%